ANALISIS KEBUTUHAN AIR UNTUK TANAMAN DAN PENYIAPAN LAHAN DAERAH IRIGASI DESA MUKTI LESTARI KAB. KUTAI TIMUR - Yayuk Srisundari (Universitas 17 Agustus 1945 Samarinda, 2011)
ANALISIS KEBUTUHAN AIR UNTUK TANAMAN DAN PENYIAPAN LAHANDAERAH IRIGASI DESA MUKTI LESTARI KABUPATEN KUTAI TIMURWater Requirement Analysis for Crops and Land Cultivation in the Village Irrigation Unitof Mukti Lestari Village, East Kutai DustrictYayuk Sri SundariFakultas Teknik, Universitas 17 Agustus 1945 SamarindaSamarinda ABSTRACTWater requirement for paddy and secondary food crops (palawija) was mostly required for land preparation and its requirement was measured by estimating the water debit capacity and determining the proper irrigation flow dimension, both technically and water effiency. The highest evapotranspiration (ETo) occurred in August with 3.95 mm/hr and the lowest one was in june with only 2.91 mm/hr. Effective rainfall of paddy crop refered to Table 1 whereas for palawija was Table 2. Soil tillage that lasted for 35 days, requirement of water ranged 2.29-2.67 mm/hr (refer to Table 3). To gain Total irrigation efficiency (e) of 65%, water required for cropping patterm paddy-paddy palawija that planted in August is 2.67 mm/hr (NFR), 0.3090 lt/ha (DR). Whereas, the water debit planned for main channel is 0.50 lt/dt/ha, 0.40 lt/dt/ha for secondary channel,and 0.35 lt/dt/ha for tertiary channel. Furthemore, the dimension (H) for main channel was 1.00 m, subsequently 0.55 m for secondary channel and 0.45 m for tertiary channel.Key words : Crop water requirement, Land preparation.